2003
DOI: 10.1046/j.1095-8649.2003.00171.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and reproduction of the cavefish Trichomycterus chaberti and the related epigean Trichomycterus cf. barbouri

Abstract: Hypogean and epigean populations of Trichomycterus catfishes inhabit streams from different environments (cave, headwater, canyon and valley) in the Torotoro National Park in the Andes, Bolivia. A significant reduction in the diameter of the eyes and in the surface area of the mesencephalon was observed in subterranean populations, along with an increase in the surface area of the telencephalon. Contrary to expectations, the barbel did not appear to be longer in hypogean populations. The observed pattern of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
1
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 30 publications
2
23
1
6
Order By: Relevance
“…Anal-fin rays 13, occasionally 12 or 14, dorsal-fin spines 7-8; dorsal-fin rays 16-18, usually 17-18; pectoralfin rays 14-17, usually 16; pelvic-fin rays 3-4, with a high degree of asymmetry; branched caudal-fin rays 9; lateral-line pores 32-36, modally 35; infraorbital pores 8-9, modally 9; preoperculomandibular pores 10-12, modally 11, post-maxillary pore present; median chin pores 2, rarely 1; enlarged mandibular pores 3, 4 and 6 (Burr et al 2001). Several studies have found evidence of asymmetry in eye size in slightly to moderately microthalmic cave species (Wilkens 2001;Pouilly & Miranda 2003); however, we found no evidence of asymmetry in the eyes of C. specus. Eye volume, eye lens and dermal cornea of the eye were also significantly reduced in C. specus when compared to C. carolinae.…”
Section: Carolinae Black River Race C T T T T T a T T A Ccontrasting
confidence: 99%
“…Anal-fin rays 13, occasionally 12 or 14, dorsal-fin spines 7-8; dorsal-fin rays 16-18, usually 17-18; pectoralfin rays 14-17, usually 16; pelvic-fin rays 3-4, with a high degree of asymmetry; branched caudal-fin rays 9; lateral-line pores 32-36, modally 35; infraorbital pores 8-9, modally 9; preoperculomandibular pores 10-12, modally 11, post-maxillary pore present; median chin pores 2, rarely 1; enlarged mandibular pores 3, 4 and 6 (Burr et al 2001). Several studies have found evidence of asymmetry in eye size in slightly to moderately microthalmic cave species (Wilkens 2001;Pouilly & Miranda 2003); however, we found no evidence of asymmetry in the eyes of C. specus. Eye volume, eye lens and dermal cornea of the eye were also significantly reduced in C. specus when compared to C. carolinae.…”
Section: Carolinae Black River Race C T T T T T a T T A Ccontrasting
confidence: 99%
“…Cave-living organisms provide a unique opportunity to investigate life history evolution, because they have colonized a radically different habitat and, in some cases, the surface-dwelling ancestor is available for comparison. Life histories of cave animals are generally characterized by shifts towards longer life and generation times, older age at first reproduction and increased brood care behaviour, as well as a decreased fecundity combined with an increase in individual offspring size (Collembola: Christiansen 1965; Gammarus minus (Amphipoda): Culver et al 1995; Teleostei: Amblyopsis rosae (Amblyopsidae) : Winemiller 1992; Astyanax mexicanus (Characidae): Hüppop and Wilkens 1991; Trichomycterus chaberti (Trichomycteridae): Pouilly and Miranda 2003; for a review see Parzefall 2000). These traits were mostly interpreted as adaptations to food scarcity (Culver 1982;Hüppop 2000), because caves are usually nutrient-poor due to a lack of photoautotrophic primary production and reliance on nutrient-influx from epigean habitats (Poulson and Lavoie 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Later, inventory studies were carried out by Lauzanne & Loubens (1985), Santos (1986Santos ( , 1991, Lauzanne et al (1990), Loubens et al (1992), Viana (1999), Barthem et al (2003), Pouilly & Miranda (2003), , Pouilly & Rodrigues (2004), , Torrente-Vilara et al (2005), Camargo & Giarrizzo (2007) and Rapp Py-Daniel et al (2007), some of them containing important ecological information about the fish assemblages. However, only Torrente-Vilara et al (2005), a report study, presents data about the general composition of the fish community near the area of the rapids of Santo Antonio Falls.…”
Section: Introductionmentioning
confidence: 99%